Hunters, rangers, cougars, and jaguars: human and nonhuman territories at the Argentine-Brazilian border, 1960s-1990s - Frederico Freitas (História, Ciências, Saúde: Manguinhos, 2022)
Abstract This article aims to understand the role of territorial practices in the interaction between human and nonhuman animals. It focuses on the Iguazú and Iguaçu national parks, established by Argentina and Brazil in the 1930s as nature reserves bisected by an international boundary. In a setting where human-made boundaries overlay natural boundaries, qualitatively different spatial practices clash in the territorial encounters between cougars, jaguars, and humans. The article demonstrates how changes in the border practices of park officials, hunters, and big cats reshuffled the terms of these encounters. The article assesses when, where, and how these encounters between rangers, poachers, and big cats took place, showing how felids challenged the spatial placement and taxonomical categories attributed to them by humans.